SOCIO-CULTURAL ROLE OF WOMEN IN CHINESE SOCIETY (Journal of Oriental Studies, 2019)
It is known that the future of the nation is closely linked with the sovereignty of the country. The future of the nation is the birth of the young generation, directly related to the social status of women in modern society, who are entrusted with national education. The role and place of women in the lit- erature, culture, religion and mentality of each country is determined. Scientists believe that women in eastern countries have a strong commitment from an early age, with strict rules and wise words. In this article, we describe the socio-cultural role of women in Chinese society.Key words: female, Chinese, gender equality, socio-cultural role, feminist.